Zoonotic infection with Onchocerca dewittei japonica in an 11-year-old boy in Kansai Region, Western Honshu, Japan. Issue 5 (October 2017) - Uni, Shigehiko; Fukuda, Masako; Ogawa, Kou; Lim, Yvonne Ai-Lian; Agatsuma, Takeshi; Bunchom, Naruemon; Saijuntha, Weerachai; Otsuka, Yasushi; Bhassu, Subha; Mat Udin, Ahmad Syihan; Zainuri, Nur Afiqah; Omar, Hasmahzaiti; et al.
Abstract: An 11-year-old boy living in Otsu City, Shiga Prefecture, Kansai Region, Western Honshu, Japan had zoonotic onchocercosis. The patient developed a painful swelling on the little finger of his left hand. The worm detected in the excised mass had external transverse ridges but did not have inner striae in the cuticle. On the basis of the parasite's histopathological characteristics, the causative agent was identified as a female Onchocerca dewittei japonica (Spirurida: Onchocercidae). The species of the filarial parasite was confirmed by sequencing the cox 1 gene of the parasite. The Japanese wild boar Sus scrofa leucomystax is a definitive host for O. dewittei japonica, which is then transmitted by blackflies as the vector to humans. The current case described occurred in the Kansai Region, Western Honshu, where such infections were previously not reported. Graphical abstract: Highlights: An 11-year-old boy living in Kansai Region, Western Honshu, Japan contracted zoonotic onchocercosis. Histopathological and molecular characteristics identified causative agent as female Onchocerca dewittei japonica . The new case of zoonotic onchocercosis was found in a region, where such infection had not been previously reported.